2013
DOI: 10.1186/1750-1326-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and neurotoxicity of recombinant α-synuclein aggregates initiated by dimerization

Abstract: BackgroundAggregation of the α-Synuclein (α-Syn) protein, amyloid fibril formation and progressive neurodegeneration are the neuropathological hallmarks of Parkinson's Disease (PD). However, a detailed mechanism of α-Syn aggregation/fibrillogenesis and the exact nature of toxic oligomeric species produced during amyloid formation process are still unknown.ResultsIn this study, the rates of α-Syn aggregation were compared for the recombinant wild-type (WT) α-Syn and a structurally relevant chimeric homologous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 57 publications
4
66
1
Order By: Relevance
“…These oligomers were morphologically higherorder aggregates of heterogeneous size, such as annular and amorphous protofibrillar oligomers [122], consistent with the heterogeneity described in other studies.…”
Section: Multimeric Intermediates: Defining the Identity And Pathogensupporting
confidence: 90%
See 2 more Smart Citations
“…These oligomers were morphologically higherorder aggregates of heterogeneous size, such as annular and amorphous protofibrillar oligomers [122], consistent with the heterogeneity described in other studies.…”
Section: Multimeric Intermediates: Defining the Identity And Pathogensupporting
confidence: 90%
“…Most recently it was shown that specific forms of α-synuclein oligomers, including β-sheet-containing dimers [122] and HNE-modified [248] α-synuclein, seed the formation of oligomeric aggregates. For example, when injected into the hippocampi of wild-type mice, the dimer-derived oligomers, but not freshly dissolved α-synuclein or insoluble fibrils, promoted apoptosis [122].…”
Section: α-Synuclein "Strains" and Prion-like Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…a-Synuclein dimerization can accelerate the formation of neurotoxic aggregates and amyloid fibrils, which may be crucial to PD pathology at the molecular level (56). Western blot analysis revealed a threefold increase of a-synuclein monomer, dimer, and oligomer in MPTP-injured mice ( …”
Section: Effects Of Dmf Treatment On Emotional Statementioning
confidence: 99%
“…[76][77][78] Nevertheless, these transmissions are far from neuronal invasion, probably due to limitations on the spread of a-synuclein aggregates. On the one hand, the fact that both mature fibers and oligomers (the most transmissible material) display high neuronal toxicity [79][80][81][82] and on the other, the added difficulty of having to be secreted to reach distant neurons, could be key factors that impede the prion capacity of a-synuclein aggregates. Very importantly at this point, it has been shown that cells normally secrete a-synuclein into their surrounding media; this opens up the possibility that oligomers of a-synuclein could be spread and act as prions.…”
mentioning
confidence: 99%